Antibody Repertoires Identify β-Tubulin as a Host Protective Parasite Antigen in Mice Infected With Trypanosoma cruzi - Montalvão, Fabricio; Nascimento, Danielle Oliveira; Nunes, Marise P.; Koeller, Carolina M.; Morrot, Alexandre; Lery, Leticia Miranda S.; Bisch, Paulo M.; Teixeira, Santuza M. R.; Vasconcellos, Rita; Freire-de-Lima, Leonardo; Lopes, Marcela F.; Heise, Norton; et al. (Frontiers in Immunology, 2018)
Few studies investigate the major protein antigens targeted by the antibody diversity of infected mice with Trypanosoma cruzi. To detect global IgG antibody specificities, sera from infected mice were immunoblotted against whole T. cruzi extracts. By proteomic analysis, we were able to identify the most immunogenic T. cruzi proteins. We identified three major antigens as pyruvate phosphate dikinase, Hsp-85, and β-tubulin. The major protein band recognized by host IgG was T. cruzi β-tubulin. The T. cruzi β-tubulin gene was cloned, expressed in E. coli, and recombinant T. cruzi β-tubulin was obtained. Infection increased IgG reactivity against recombinant T. cruzi β-tubulin. A single immunization of mice with recombinant T. cruzi β-tubulin increased specific IgG reactivity and induced protection against T. cruzi infection. These results indicate that repertoire analysis is a valid approach to identify antigens for vaccines against Chagas disease.